Application Of The Dijkstra Algorithm To Determine The Shortest Route From City Center Surabaya To Historical Places - Hanna Pratiwi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Abstract Historic places are places that are often visited by local residents and even tourists from outside the city and abroad. Historic places are places that must be visited by tourists from outside the area, but there are problems that often occur when they want to visit the destinations of this historic place. The problem is the route from each historical site location itself and also the ignorance of the shortest and fastest routes that are more efficient. This study aims to determine the shortest route that will use Dijkstra's Algorithm as a research method. This research will be accompanied by determining which points will be passed so that they can get the shortest route so as to reduce driving time. It will also be accompanied by how to use Dijkstra's Algorithm in finding the shortest route for the location of this historic place. The results obtained from this study there are 4 shortest routes that can be taken to get to historical places through the starting point Gubeng Station.